Optogenetic deconstruction of sleep-wake circuitry in the brain - Adamantidis, Antoine; Carter, Matt C.; De Lecea, Luis (Frontiers in Molecular Neuroscience, 2010)
How does the brain regulate the sleep-wake cycle? What are the temporal codes of sleep- and wake-promoting neural circuits? How do these circuits interact with each other across the light/dark cycle? Over the past few decades, many studies from a variety of disciplines have made substantial progress in answering these fundamental questions. For example, neurobiologists have identified multiple, redundant wake-promoting circuits in the brainstem, hypothalamus, and basal forebrain. Sleep-promoting circuits have been found in the preoptic area and hypothalamus. One of the greatest challenges in recent years has been to selectively record and manipulate these sleep-wake centers in vivo with high spatial and temporal resolution. Recent developments in microbial opsin-based neuromodulation tools, collectively referred to as “optogenetics,” have provided a novel method to demonstrate causal links between neural activity and specific behaviors. Here, we propose to use optogenetics as a fundamental tool to probe the necessity, sufficiency, and connectivity of defined neural circuits in the regulation of sleep and wakefulness.